Should heart failure patients be left to fate? Temporary implementation of veno-arterial extracorporeal membrane oxygenation for haemodynamic support during excision of rectal carcinoma in an end-stage biventricular heart failure patient. (26th July 2018) - Hergesell, Vera; Mathew, Erwin; Kornprat, Peter; Knez, Igor; Mischinger, Hans-Joerg; Dapunt, Otto; Spiliopoulos, Sotirios
Management of end-stage heart failure patients requiring major general surgery is not well defined. Due to poor cardiorespiratory reserve, perioperative morbidity and mortality are excessively high. We report a case of temporary implementation of veno-arterial extracorporeal membrane oxygenation for haemodynamic support during excision of rectal carcinoma in an end-stage heart failure patient and describe perioperative management.